FREE HEALTH SCREENING TO DETECT RISK FACTORS OF NON-communicable diseases (PTM) IN RIJALI KELURAHAN, SIRIMAU DISTRICT, AMBON CITY REGENCY: FREE HEALTH SCREENING TO DETECT RISK FACTORS OF NON-communicable diseases (PTM) IN RIJALI KELURAHAN, SIRIMAU DISTRICT, AMBON CITY REGENCY - Christiffol Leiwakabessy; Yane Sentia Werluka; Triska Ereh; Ilona Miranda Tuhuleruw; Marlon Tahapary; Godlife Wattimury; Febry Hitipeuw; M Rivaldi Tawainella; Seplinovye P. Maruanaya; Agnes Mirel Kailola; Zepty Fenc Tiwery; Stevian Huwae Junior; Ahmad Muhajir Rumaf; Nadillah Wattimena (Jurnal Pengabdian Ahmad Yani, 2021)
Non-communicable diseases (NCDs) are one of the main causes of death worldwide. In 2016, 73% of deaths in Indonesia were estimated to be due to NCDs, of which 35% were caused by cardiovascular disease, 12% cancer, 6% acute respiration, 6% diabetes, and 15% other NCDs (World Health Organization, 2018). In Indonesia, the results of Riskesdas 2018 show that the prevalence of the population with high blood pressure is 34.11%. The prevalence of high blood pressure in women (36.85%) was higher than that of men (31.34%). The prevalence in urban areas is slightly higher (34.43%) than in rural areas (33.72%). Control of Non-Communicable Diseases (NCDs) begins with early detection of risk factors. Early detection of Non-Communicable Diseases (NCDs) that can be done in the form of measuring blood pressure, detecting blood sugar, cholesterol and uric acid levels, measuring height and weight, and abdominal circumference. The purpose of holding free screenings as one of the priority programs for Real Work Class is to provide services as well as provide counseling about the importance of early detection of risk factors for Non-Communicable Diseases (NCDs). As a result of the dedication carried out by many people who were enthusiastic about participating in this free screening. The final result expected from the implementing team is that the community will increase their awareness to carry out early detection of NCDs risk factors at the puskesmas once a month, especially for people who have the final result will be at risk of contracting non-communicable diseases.